The Effects of Combined Use of Ovarian Needle Puncture and Platelets Rich Plasma on Ovarian Total Antioxidants Capacity (TAC) Level and ICSI Outcome in PCOS Women - Abunyla , Rawaa Saad; Al-Anbari , Lubna Amer; Al-Obaidi , Manal Taha (American Journal of Biomedicine and Pharmacy, 2025)
Background: Hyperandrogenism, ovulatory dysfunction, abnormal GnRH pulsation leading to irregular gonadotropin secretion all contribute to PCOS. Platelet Rich Plasma (PRP) are increasingly used for various disorders, including infertility, and is effective for ovarian rejuvenation via improving folliculogenesis. Objectives: To estimate the effects of combined use of Ovarian Needle Puncture and PRP on ovarian total antioxidant capacity and ICSI cycle characteristics and outcome in PCOS Women Patients and Methods: This study involved seventy women of infertile couples; patients were randomly allocated into two groups: PRP Group (35 women): Patients who underwent simultaneous use of Ultrasound-guided trans-vaginal ovarian needle puncture and PRP in the preceding cycle of ICSI cycle. Non PRP Group (35 women): Patients who didn’t undergo simultaneous use of Ultrasound-guided trans-vaginal ovarian needle puncture and PRP in the preceding cycle of ICSI cycle. CD7-CD8: Ultrasound-guided trans-vaginal ovarian needle puncture coincided with ovarian PRP was done under general light anesthesia for PRP group. Total antioxidant capacity was measured in the follicular fluid collected on the day of oocyte retrieval. Results: There were no notable differences between PRP and Non-PRP groups in stimulation, oocyte, embryo characteristics, or ovarian total antioxidant capacity levels on ova pick up- day. Pregnancy rates were higher in the PRP group for both fresh (34.3% vs 20.0%, P < 0.113) and frozen ET (20.0% vs 14.3%, P < 0.292), though not statistically significant. Conclusion: Although the combined use of ovarian needle puncture and platelet-rich plasma (PRP) did not produce significant effects on ovarian total antioxidant capacity (TAC) levels or on oocyte and embryo yield in women with PCOS, the cumulative pregnancy rate was higher following this intervention. These findings suggest the need for further large-scale studies to confirm the potential benefits of this approach.